2002
DOI: 10.1097/00042728-200202000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Cardiac Arrest After Polidocanol Sclerotherapy of Peripheral Venous Malformation

Abstract: background. Polidocanol sclerotherapy is a well-established therapeutic modality for the treatment of venous malformations. Systemic complications are extremely rare. objective. To report a case of cardiac complication after polidocanol injection of peripheral venous malformation. methods. A case report and a review of the English language literature using a published MEDLINE search strategy. results. A patient undergoing polidocanol sclerotherapy for a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 8 publications
0
38
0
2
Order By: Relevance
“…Until now, very few severe systemic complications have been reported, including cardiac complications, neurologic deficits, pulmonary embolism, and stroke [46,[49][50][51][52][53]. In our study, one patient (patient 1) experienced a complication.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Until now, very few severe systemic complications have been reported, including cardiac complications, neurologic deficits, pulmonary embolism, and stroke [46,[49][50][51][52][53]. In our study, one patient (patient 1) experienced a complication.…”
Section: Discussionmentioning
confidence: 57%
“…According to the manufacturer's guidelines, the maximum daily dose of polidocanol based on body weight is 2 mg/kg/day [45]. Theoretically, systemic complications such as cardiotoxicity can occur after the systemic diffusion of polidocanol, when it passes into the systemic circulation from the injection site, such as during varicose vein treatment [46]. However, in BRTO, polidocanol has no chance to pass into the systemic circulation from the injection site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polidocanol is a nonionic detergent sclerosing agent. Its detergent action induces a rapid overhydration of endothelial cells, leading to vascular injury [24]. The current study indicated that polidocanol sclerotherapy has significant efficacy in pain relief in patients with painful VMs.…”
Section: Discussionmentioning
confidence: 59%
“…To prevent adverse reactions, excessive usage of polidocanol should be avoided. Marrocco-Trischitta et al [24] reported one incident of reversible cardiac arrest in a 5-year-old patient with a VM following injection of 4 mL of 1% polidocanol. Cardiac complications following polidocanol injections are extremely rare, but they can occur owing to the anesthetic properties of polidocanol [24].…”
Section: Discussionmentioning
confidence: 99%